Bacterial degradation of milk components is affected by storage temperature and time - S. Zimmerman; I.J. Jeon; L. McVay; E. Ferdinand (Kansas Agricultural Experiment Station Research Reports, 2001)
Raw milk is an excellent medium for bacterial growth. The objective of this study was to evaluate the number of microbes and component degradation in raw milk. Milk fat content did not affect bacteria counts. As storage temperature or time increased, greater numbers of bacteria were present. In this study, milk protein was degraded preferentially over lactose or milk fat. As the milk storage temperature increased from 39 to 45°F, protein degradation became more pronounced. Milk fat remained relatively stable, though some degradation products were observed, especially after 4 days of storage at 39°F. Both milk fat and protein degradation can produce small, volatile compounds that negatively affect the flavor and odor of milk. Thus, to maintain high quality fluid milk in the market, milk must be available to the consumer soon after its processing.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Raw milk quality; Proteolysis; Lipolysis